Signaling pathways governing the maintenance of breast cancer stem cells and their therapeutic implications - Ordaz-Ramos, Alejandro; Tellez-Jimenez, Olivia; Vazquez-Santillan, Karla (Frontiers in Cell and Developmental Biology, 2023)
Breast cancer stem cells (BCSCs) represent a distinct subpopulation of cells with the ability to self-renewal and differentiate into phenotypically diverse tumor cells. The involvement of CSC in treatment resistance and cancer recurrence has been well established. Numerous studies have provided compelling evidence that the self-renewal ability of cancer stem cells is tightly regulated by specific signaling pathways, which exert critical roles to maintain an undifferentiated phenotype and prevent the differentiation of CSCs. Signaling pathways such as Wnt/β-catenin, NF-κB, Notch, Hedgehog, TGF-β, and Hippo have been implicated in the promotion of self-renewal of many normal and cancer stem cells. Given the pivotal role of BCSCs in driving breast cancer aggressiveness, targeting self-renewal signaling pathways holds promise as a viable therapeutic strategy for combating this disease. In this review, we will discuss the main signaling pathways involved in the maintenance of the self-renewal ability of BCSC, while also highlighting current strategies employed to disrupt the signaling molecules associated with stemness.